The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3892/ol.2017.7572
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-colony stimulating factor producing mucinous cystic neoplasm with an associated invasive carcinoma of the pancreas

Abstract: Abstract. The present case study documents an autopsy case of granulocyte-colony stimulating factor (G-CSF)-producing mucinous cystic neoplasm (MCN), with an associated invasive carcinoma of the pancreas. A 65-year-old woman presented to Omuta City Hospital (Omuta Japan) with a primary complaint of abdominal pain. Multiple liver nodules and a pancreatic cyst were detected upon abdominal computed tomography. Initially, liver abscess was suspected as the patient exhibited leukocytosis and elevated C-reactive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Moreover, we have shown that patients with cervical intraepithelial neoplasia exhibited an increase in the frequency of circulating CD66b + low density neutrophils, again indicating systemic effects of these lesions, even before progressing to cancer [17]. Besides HPV associated cancers, other types of solid tumors can induce leukocytosis, including pancreas, non-small lung and colorectal cancer [4143]. Leukocytosis can lead to the accumulation of MDSC that inhibit T cell responses, and by extension hamper anti-tumor cell cytotoxic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have shown that patients with cervical intraepithelial neoplasia exhibited an increase in the frequency of circulating CD66b + low density neutrophils, again indicating systemic effects of these lesions, even before progressing to cancer [17]. Besides HPV associated cancers, other types of solid tumors can induce leukocytosis, including pancreas, non-small lung and colorectal cancer [4143]. Leukocytosis can lead to the accumulation of MDSC that inhibit T cell responses, and by extension hamper anti-tumor cell cytotoxic activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies have evaluated the pattern of necrosis in G-CSF-producing tumors, and further research is needed in this respect. There are many case reports of G-CSF-producing tumors initially treated with antibiotics because of misdiagnosis as abscesses [ 5 , 39 – 46 ]. In our cases 3 and 4, the imaging findings were very similar to liver abscess (Fig.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Renal lesions include aCN, [24][25][26][27][28][29][30] and the related lesion, MEST of the kidney, 24,26,27,[29][30][31][32][33] as well as angiomyolipoma with epithelial cysts. [34][35][36] There is also mucinous cystic neoplasm of the pancreas [37][38][39][40][41][42][43][44][45]65 and of the liver. 39,42,46,47 A common theme in these lesions is a female predominance and reference to the stroma around the cysts as being "ovarian" or "Müllerian" in appearance.…”
Section: Discussionmentioning
confidence: 99%
“…5,23 In contrast, a female predominance is also known to occur in a small number of pathologic lesions, not considered to be part of the DICER1 tumor predisposition syndrome, and not involving the female reproductive system. Most are renal lesions, including adult cystic nephroma (aCN), [24][25][26][27][28][29][30] mixed epithelial-stromal tumor (MEST) of the kidney, 24,26,27,[29][30][31][32][33] and angiomyolipoma with epithelial cysts; [34][35][36] but there are other non-renal lesions, including mucinous cystic neoplasm of the pancreas [37][38][39][40][41][42][43][44][45] and of the liver. 39,42,46,47 The strong predominance of female patients raises the question as to whether these lesions are, at least in part, hormonally driven.…”
mentioning
confidence: 99%
See 1 more Smart Citation